COUNTING S_5-FIELDS WITH A POWER SAVING ERROR TERM. (1st May 2014) - SHANKAR, ARUL; TSIMERMAN, JACOB
Abstract: We show how the Selberg Λ ^2 -sieve can be used to obtain power saving error terms in a wide class of counting problems which are tackled using the geometry of numbers. Specifically, we give such an error term for the counting function of S_5 -quintic fields.